The Role of Corporate Governance and Ethics in Facing the Challenges of Digital Transformation - Herikson Tampubolon (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2026)
This study aims to analyze the role of corporate governance and ethics in supporting the success of organizational digital transformation, particularly in facing increasingly complex digital risks and challenges. This study uses a qualitative approach with a case study design, in which data is collected through in-depth interviews with key informants and analysis of policy documents related to governance, risk management, and digital ethics. The results show that digital transformation presents major challenges in the form of data security and privacy risks, dependence on digital systems and third parties, unclear oversight responsibilities, and pressure to comply with dynamic digital regulations. The findings also reveal that corporate governance plays an important role as a control mechanism for digital transformation through strategic oversight, accountability, and risk management, while ethics serves as a normative foundation that guides the responsible, fair, and transparent use of technology. The integration of corporate governance and ethics has been proven to strengthen the legitimacy of digital policies, increase stakeholder trust, and serve as an important indicator of the success of sustainable digital transformation. This research has implications for the development of a conceptual model of digital transformation that emphasizes an integrated approach to technological innovation, governance, and ethical values in an organizational context.